Avaliação de memória viso-espacial e verbal de musicistas e não musicistas - Tormin, Malba Cunha (2008)
This study investigated differences in performance of musicians and non musicians on working memory tests, based on Alan Baddeley´s model which refers to an integrate model of active memory that covers visual-spatial registers specialized in the visual and/or spatial codification and other registers of phonological nature specialized in the verbal codification supervised by a central executive. This memory system is linked to an active and simultaneous information processor as well as to its transitory storer, fundamental in activities that demand reasoning and quick information, very present in music. In this research adaptations were made to the pictoric memory test (TEPIC-M) to make it possible to investigate the processing of short time visual-spatial information through recall tasks. The aim of this study was to evaluate if there were differences between musicians and non musicians in the processing of visual-spatial and verbal information and if the study of music may influence the abilities tested by the recall tasks. Research was performed with Music, Language and Literature and Engineering university students at the Uberlândia Federal University. Results were obtained by mixed variance analysis (ANOVA 2X2X3) for the experimental factors and indicated that the musicians had intermediate behavior in regards to non musicians but not superior, in a way that they were close to the Language and Literature students in verbal visual-spatial information processing. These data suggests that the study of music covers and develops visual-spatial and verbal memory mechanisms. Another important result was that the Engineers got a greater number of points in visual-spatial memory, independent of the stimulus of the levels of the demanded tasks in the memory tests. Also the Superlearning effect of the verbal code was detected in all of the 3 studied groups, as the results indicated greater efficiency in the decodifying and verbal reflection of the word stimulus. Finally, results may corroborate also for incentives for musical education to be applied in public and private schools in the country, integrating cognitive psychology and musical education areas aiming to open up research fields in the processes of cognitive development and musical learning, intensifying the study of music in Brasil.